Laboratory and clinical aspects of human papillomavirus testing - Chan, Paul K.S. (Informa Healthcare, 2012)
Human papillomavirus (HPV) infection is associated with a wide spectrum of disease that ranges from self-limited skin warts to life-threatening cancers. Since HPV plays a necessary etiological role in cervical cancer, it is logical to use HPV as a marker for early detection of cervical cancer and precancer. Recent advances in technology enable the development of high-throughput HPV assays of different formats, including DNA-based, mRNA-based, high-risk group-specific and type-specific methods. The ultimate goal of these assays is to improve the accuracy and cost-effiectiveness of cervical screening programs. HPV testing has several potential advantages compared to cytology-based screening. However, since the cancer to transient infection ratio is always low in the general population, HPV test results are bound to have a low positive predictive value that may subject women to unnecessary follow-up investigations. The wide-spread administration of prophylactic HPV vaccine will substantially decrease the incidence of cancer and precancer. This poses a number of challenges to cytology-based screening, and the role of HPV testing is expected to increase. Finally, apart from technical and cost-effiectiveness considerations, one should also keep in mind the psycho-social impact of using sexually-transmitted agents as a marker for cancer screening.